2008
DOI: 10.1186/1744-859x-7-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of anxiety and depression in patients with bronchial asthma, chronic obstructive pulmonary disease and tuberculosis in a general hospital of chest diseases

Abstract: BackgroundDepression necessitating assistance from health professionals has a lifetime prevalence of 10%. Chronic disease increases comorbidity with mood and/or anxiety disorders. Patients with chronic pulmonary disease present with severely impaired functionality, chronic somatic and psychogenic pain, require frequent hospitalizations and have a dependency upon medical and nursing personnel. In the present study we assessed anxiety and depression in patients hospitalized for pulmonary disease in a pulmonary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
4
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 18 publications
7
80
4
6
Order By: Relevance
“…Since our understanding of the possible contribution of infectious processes to the occurrence of mental disorders is still in its infancy [36], further research is needed to scrutinize this relationship. Fifth, although high prevalence of anxiety and depression in individuals with chronic breathing disorders has been reported [37][38][39], the pathophysiological mechanisms underlying these relationships remain unclear [40]. As several researchers have suggested [41][42][43][44], there is a need to routinely employ screening tools for anxiety and depression in nonpsychiatric medical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Since our understanding of the possible contribution of infectious processes to the occurrence of mental disorders is still in its infancy [36], further research is needed to scrutinize this relationship. Fifth, although high prevalence of anxiety and depression in individuals with chronic breathing disorders has been reported [37][38][39], the pathophysiological mechanisms underlying these relationships remain unclear [40]. As several researchers have suggested [41][42][43][44], there is a need to routinely employ screening tools for anxiety and depression in nonpsychiatric medical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Depression scores, as measured by the Beck Depression Inventory, were less pronounced in these patients (CA 20%, UA 49%, COPD 29%) but nevertheless a cause for concern. In a similar study on 132 pulmonary disease patients in a Greek hospital, Moussas et al (42) found that a total of 49.2% showed moderate or severe depression and 26.5% had anxiety. Fernandes et al (19) demonstrated a positive association of higher degrees of asthma severity with increased anxiety.…”
Section: Fig 3 Group Mean Ventilatory Response To Itto For Experimementioning
confidence: 99%
“…Our animal model of reversible tracheal obstructions, ITTO, thus mimics one component of asthma. It is well acknowledged that respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD), are associated with significantly higher rates of anxiety and depression compared with the general population (42). In addition, there are significantly more individuals suffering from a respiratory or lung disease with panic disorder or major depression than individuals without such a respiratory diagnosis (22).…”
Section: Fig 3 Group Mean Ventilatory Response To Itto For Experimementioning
confidence: 99%
“…This is further worsened by co-infection with HIV [27][28][29]. Several studies have established comorbidity of TB and mental health disorders especially depression [32,[61][62][63][64][65]. It also important to note that just as HIV predisposes the individual to tuberculosis infection by lowering the immunity, depression has also been associated with decreased immunity, therefore both illnesses can synergistically cause a more profound reduction in immunity resulting in excess vulnerability to tuberculosis infection [65].…”
Section: Introductionmentioning
confidence: 99%